Personal Data Breach Cases In Indonesia : Perspective Of Personal Data Protection Law - Tanti Kirana Utami; Kayla Andini Putri; Salsa Octaviani Suryanto; Fina Asriani (Indonesian Journal Publisher, 2025)
This research aims to analyse the situation and frequency of personal data breach cases in Indonesia, identify the factors causing them, and evaluate the preventive efforts that have been made in the context of the Personal Data Protection Law. This research uses a mixed methods approach that combines quantitative and qualitative methods. Quantitative data was obtained through an online survey of Indonesians to measure the level of awareness and experience related to personal data breaches. Meanwhile, qualitative data was obtained through a literature study and in-depth interviews with experts in cybersecurity and law. The results show that cases of personal data breaches in Indonesia are increasing, with the main contributing factors including weak public awareness, lack of data protection by companies, and suboptimal law enforcement. Preventive efforts that need to be improved include socialisation of the Personal Data Protection Law, improving information system security, and cross-sector cooperation. This research provides recommendations for more effective policies to prevent and address cases of personal data breaches in the future.